2008
DOI: 10.1007/s10384-008-0598-7
|View full text |Cite
|
Sign up to set email alerts
|

Ballooning canaliculoplasty after lacrimal trephination in monocanalicular and common canalicular obstruction

Abstract: Balloon canaliculoplasty after lacrimal trephination is a simple and safe method that may be a good alternative treatment for common canalicular and distal canalicular obstructions, before resorting to conjunctivodacryorhinostomy with Jones tube insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…Compared with the single-stent group, no significant complications appeared, which was consistent with previous reports [11][12][13][14][15]. The other treatment methods implicated for canalicular obstruction are DCR combined with membranectomy [5,6], trephination and silicone tube stenting [7,16], ballooning with/without silicone stenting [17,18], ballooning canaliculoplasty following lacrimal trephination [8], and intraoperative use of mitomycin C [9,10]. The success rates of these procedures vary in the range of 25-92% with the majority being under 50-60% (Table 7).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Compared with the single-stent group, no significant complications appeared, which was consistent with previous reports [11][12][13][14][15]. The other treatment methods implicated for canalicular obstruction are DCR combined with membranectomy [5,6], trephination and silicone tube stenting [7,16], ballooning with/without silicone stenting [17,18], ballooning canaliculoplasty following lacrimal trephination [8], and intraoperative use of mitomycin C [9,10]. The success rates of these procedures vary in the range of 25-92% with the majority being under 50-60% (Table 7).…”
Section: Discussionsupporting
confidence: 86%
“…For canalicular obstruction, the cause of failure is restenosis or sticky adhesive changes of the canaliculus following the removal of the silicone tube [5][6][7][8][9][10]. We reasoned that the insertion of a wider stent would make the canalicular pathway more patent and aid in maintaining the clearance of the pathway following removal of the tube.…”
Section: Introductionmentioning
confidence: 95%
“…5 Yang employed trephination followed by balloon canaliculoplasty in patients with distal monocanalicular and CCO with success rates of 54%. 8 Trephination and intubation during EnDCR surgery has not been widely reported. In a small series of five patients, Nemet reported symptomfree results in four out of five patients following EnDCR with trephination and application of mitomycin C (MMC) in distal and CCO where the obstruction was at least 7 mm from the punctum.…”
Section: Discussionmentioning
confidence: 99%
“…Some techniques can be performed in an office setting, while others are used as an adjunct to more invasive lacrimal surgery. [2][3][4][5][6][7][8] In the setting of transnasal endoscopic dacryocystorhinostomy (EnDCR), one previous study has reported retrospective outcomes of trephination for CCOs. 9 To our knowledge, this is the first study that has employed membranectomy without trephination and has attempted to evaluate the outcome of both membranous and more solid distal obstructions of the common canaliculus.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that silicone intubation following ballooning dilation after lacrimal trephination is a simple and well tolerated method that may be a good alternative treatment for common canalicular and distal canalicular obstructions, before resorting to conjunctivodacryocystorhinostomy (CDCR) with Jones tube insertion [20 ]. Immediate clinical improvement can be achieved in 82% of cases and common canalicular obstructions have better prognosis than monocanalicular obstructions [20 ].…”
Section: Balloon Canaliculoplastymentioning
confidence: 98%